2022
DOI: 10.26434/chemrxiv-2022-26fbs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activated Carbon Electrodes with Improved Sorption Capacity for Supercapacitive Swing Adsorption of Carbon Dioxide

Abstract: Global warming due to anthropogenic CO2 emissions demands the rapid development of efficient carbon capture technologies. Supercapacitive swing adsorption (SSA) is a technology that relies on the reversible charge and discharge of supercapacitor electrodes to selectively adsorb and desorb CO2. A current limitation of SSA is the low sorption capacity. Here, we investigate a series of activated carbons derived from biomass, coke, coal, and carbide as electrode materials for SSA. The energetic and adsorptive perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We recently discovered that biomass‐derived activated carbons from garlic skin, garlic roots, and garlic clove powder lead to about 3–4 times increase of the gravimetric adsorption capacity and adsorption rate, and that there is a strong positive correlation between capacitance and CO 2 adsorption capacity. [ 12 ] Recently, Forse et al. reported that the gravimetric sorption capacity of SSA can be increased from 50 to 112 mmol kg −1 by charging the electrodes between −1 and +1 V instead of −1 and 0 V, but this approach resulted in a very high energy consumption (751 kJ mol −1 CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently discovered that biomass‐derived activated carbons from garlic skin, garlic roots, and garlic clove powder lead to about 3–4 times increase of the gravimetric adsorption capacity and adsorption rate, and that there is a strong positive correlation between capacitance and CO 2 adsorption capacity. [ 12 ] Recently, Forse et al. reported that the gravimetric sorption capacity of SSA can be increased from 50 to 112 mmol kg −1 by charging the electrodes between −1 and +1 V instead of −1 and 0 V, but this approach resulted in a very high energy consumption (751 kJ mol −1 CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…These resistance values are lesser than all the previously reported biomass‐derived electrodes used for SSA. [ 12 ] This signifies that the modified synthesis and electrode preparation procedure for garlic‐roots derived activated carbon electrodes is critical to achieve better electronic conductivity. A record low energy consumption of ≈70 kJ mol −1 is observed at −1 V (Figure 3e).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation